2019
DOI: 10.1111/jonm.12841
|View full text |Cite
|
Sign up to set email alerts
|

Manager, clinician or both? Nurse managers' engagement in clinical care activities

Abstract: In most health systems, nursing wards and departments are run by an experience registered nurse (RN) appointed to a management position, combining the clinical leadership of nurses with the managerial responsibilities of operations. These nurse managers play a crucial role in the organisation and delivery of health services: creating environments where nurses can provide quality patient care, while ensuring that organisational imperatives are met (Labrague, Abstract Aim: To explore the extent of Australian nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…First, nurse managers in the country mostly engage in dual roles-that is, performing clinical care activities. Providing patient care in addition to completing managerial responsibilities due to staff shortage in many hospitals is inherently stressful and draining (Duffield, Gardner, Doubrovsky, & Wise, 2019). Further, nurse managers face various stressors originating from high workloads, insufficient resources and challenges in budgeting (Labrague, McEnroe-Petitte, et al, 2018), which could negatively affect their overall health and well-being and may drive them to leave the organisation and the profession.…”
Section: Discussionmentioning
confidence: 99%
“…First, nurse managers in the country mostly engage in dual roles-that is, performing clinical care activities. Providing patient care in addition to completing managerial responsibilities due to staff shortage in many hospitals is inherently stressful and draining (Duffield, Gardner, Doubrovsky, & Wise, 2019). Further, nurse managers face various stressors originating from high workloads, insufficient resources and challenges in budgeting (Labrague, McEnroe-Petitte, et al, 2018), which could negatively affect their overall health and well-being and may drive them to leave the organisation and the profession.…”
Section: Discussionmentioning
confidence: 99%
“…high bed occupancy, increased admissions) and staff shortages compel nurse managers to engage in clinical care in addition to their management responsibilities. Performing these dual roles (clinical and managerial roles) has been associated with unpleasant reactions and increased stress (Duffield et al., 2019). Previous studies identified stress in nurse managers as an important precursor of toxic leadership, aside from their personality traits and skills (Astrauskaite et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the hospital type predicted toxic leadership behaviour among nurse managers. (Duffield et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in health care demands and the ever‐changing health care environment has resulted in nurse managers shouldering most of the responsibility of increasing patient and staff satisfaction (Emmons, 2018). Nurse managers at the executive level are in charge of clinical nursing services, strategic planning, administration as well as clinical leadership, while the head nurses or first‐line nurse managers are responsible for patient care activities that occur 24 hr a day in their units (Chase, 2010; Duffield, Gardner, Doubrovsky, & Wise, 2019; Gunawan & Aungsuroch, 2017). Notably, nursing managers are responsible for maintaining the link between an institution's administrative mission and the nurses who provide nursing care in the clinical unit, as well as being in charge of efficient patient care activities by ensuring that subordinate nurses are qualified for the tasks allocated to them.…”
Section: Introductionmentioning
confidence: 99%